Transrectal sentinel lymph node biopsy for early rectal cancer during transanal endoscopic microsurgery. Issue 1 (January 2014) - Arezzo, Alberto; Arolfo, Simone; Mistrangelo, Massimiliano; Mussa, Baudolino; Cassoni, Paola; Morino, Mario
Abstract Background: Local excision of invasive cancer by transanal endoscopic microsurgery (TEM) entails the risk of lymphnode metastases that obliges to radical surgery. A determination of metastatic lymph-nodes would avoid major surgery in the vast majority of cases. We applied the concept of sentinel lymphnode (SLN) biopsy to suspected invasive rectal cancers treated by TEM. Methods: Indocyanine green (ICG) is injected in the submucosa underneath the lesion. The tumor is dissected full-thickness until the perirectal fat. A near infra-red (NIR) optic provides a map of mesorectal lymphatics, on which guide the perirectal fat is dissected and lymph-nodes are excised. Results: The technique was tested in three patients. In all cases the pathologist confirmed presence of lymphnodes in the excised tissue, no case showed metastasis. In all cases final pathology of the rectal neoplasm did not indicate radical surgery. Conclusion: In suspected invasive cancers, SLN mapping could be a useful technique to identify the first lymph node receiving drainage from the tumour, whose accurate pathological examination could predict the status of the remaining nodes and indicate further radical surgery. An ongoing study on a prospective case series will assess sensitivity and negative predictive value of SLN biopsy.